Exploring Learners’ Cognitive, Affective, and Conative Responses toward Teacher Modelling Scaffolding in EFL Classrooms - Nursyafida Nursyafida; Bukhori Bukhori; Abdul Hadi (FKIP - Universitas Riau, 2026)
This study aims to explore students' cognitive, affective, and conative responses to the use of modeling as scaffolding in EFL. A descriptive qualitative approach was used, involving two English teachers and six students in a junior high school. Data were collected through classroom observations, teacher interviews, and student interviews, and analyzed using thematic analysis. The findings indicate that modeling as a supporter produces interrelated learning responses. Cognitively, modeling helps students grasp material more quickly, recognize language patterns, and generate examples independently. Affectively, modeling creates a comfortable learning atmosphere, reduces students' anxiety, and increases their confidence during the learning process. Conatively, modeling encourages students to take concrete actions, such as actively completing assignments, asking questions, participating in discussions, taking notes, and demonstrating a willingness to answer questions or perform in front of the class. These responses indicate that modeling not only supports students' understanding but also their emotional engagement and learning behaviors. The study concludes that modeling is an effective and holistic support strategy in EFL teaching, as it simultaneously influences students' cognitive understanding, emotional responses, and learning actions. These findings are expected to contribute to pedagogical practice and provide insights for teachers in implementing responsive support strategies in EFL classrooms.